Urgensi Sikap Dalam Pencapaian Hasil Belajar Mahasiswa - Jailani Jailani (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2013)
Learning is change to ability, skill and tenable somebody attitude in certain range of time. That growth that happened in learning that, that is behaviour change after student somebody get various experience in so many situation learn the itself, so that from various that experience will cause the change process that happened in x'self of student somebody. That of result of learning is entire efficiency and its result is which reached for through study process and specified with the number measured by pursuant to test of result of learning. That deed and result of learning determined in the form of accretion of knowledge items which is in the form of fact, domination form the psychomotoric, and provisions in its bearing with the personality of student somebody. In learning a learning, attitude existence one condition needed in course of study of a learning. Attitude is behaviour which swowing in face of or accept something; in course of study in a learning of there are positive attitude and student negativity to science which implied in the small fish of learning. Hence student owned by the positive attitude to a learning show the result learn reached for higher compared to by a student behaving negativity to a learning